Red cell N5-methyltetrahydrofolate concentrations and C677T methylenetetrahydrofolate reductase genotype in patients with stroke. Issue 1 (23rd December 2003) - Icke, G C; Dennis, M; Sjollema, S; Nicol, D J; Eikelboom, J W
Abstract : Aims: To investigate the relation between total red cell folate, red cell N 5 -methyltetrahydrofolate ( N 5 MTHF) concentrations, and N 5 N 10 -methylenetetrahydrofolate reductase (MTHFR) genotypes in stroke. Methods: The study comprised 120 consecutive patients presenting to hospital with acute stroke. Multivitamin supplement use was recorded. Serum and red cell folate were measured by microbiological assays using Lactobacillus casei and Enterococcus faecalis, and by the DPC-BioMediq Immulite™ 2000 analyser. Total plasma homocysteine (tHcy), serum cobalamin, and serum vitamin B6 were measured and the C677T MTHFR genotype determined. Results: There were no significant differences in blood tHcy or vitamin concentrations according to MTHFR genotype in the overall patient cohort. However, when patients taking vitamins were excluded, total red cell folate and red cell N 5 MTHF were significantly lower in patients with the TT genotype compared with CT or CC genotypes. In the overall cohort, irrespective of genotype, red cell folate was significantly lower when assayed microbiologically than with the Immulite assay. This discrepancy remained after exclusion of patients taking vitamins. Conclusion: Total red cell folate and red cell N 5 MTHF are significantly lower in stroke patients with the TT compared with the CT and TT MTHFR genotypes, particularly those not taking vitamin supplements. Microbiological assays that measure biologically active folates provide substantially lower estimates of folate than the Immulite™ assay. Because folate is a key determinant of blood homocysteine values, these findings may impact on the interpretation of the strength and independence of the association between raised blood concentrations of homocysteine and atherothrombosis risk reported in most epidemiological studies.